ANALYSIS OF ENVIRONMENTAL FACTORS AND ENTREPRENEURIAL ORIENTATION FOR THE DEVELOPMENT OF UMKM DODOL IN SERDANG BEDAGAI REGENCY WORKSHOP MARKET - Himmatul Ulya; Suhendi; Mesra B. (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
This study aims to determine and analyze the effect of environmental factors and entrepreneurial orientation on the development of MSME Bengkel Market in Serdang Bedagai Regency. The type of research used in this research is associative research with a quantitative approach. The population in this study were MSME's players in the Bengkel Market in Serdang Bedagai Regency. The sampling method uses a nonprobability sampling method with accidental sampling technique to provide questionnaires directly / by chance to meet respondents who are said to be suitable and feasible with existing research. Due to limited time, cost, other things, the number of research samples was 35 respondents. The data collection method was carried out by means of questionnaires and interviews. The data analysis method used is multiple linear regression analysis. Based on the research results obtained partially and simultaneously, it shows that environmental factors and entrepreneurial orientation have a significant effect on the development of MSME's. The results of the coefficient of determination test obtained an adjusted R square value of 0.928 (92.8%). This shows that the variables that environmental factors and entrepreneurial orientation are able to explain the development of MSME's by 92.8%, while the remaining 7.2% is influenced by other variables not examined in this study.